An α-tocopheryl succinate enzyme-based nanoassembly for cancer imaging and therapy - Song Yi Lee; Hyun-Jong Cho (Taylor & Francis Group, 2018)
Nanoassembly (NA) based on a D-α-tocopherol succinate (αTS) conjugated lysozyme (Lys) (Lys-αTS) was fabricated for tumor-selective delivery of curcumin (CUR) for breast cancer therapy. Lys and αTS were used as a biocompatible enzyme and a hydrophobic residue, respectively, for the preparation of nanocarriers in this study. Compared with CUR-loaded cross-linked Lys (c-Lys/CUR) NA, Lys-αTS/CUR NA exhibited a smaller hydrodynamic size (213 nm mean diameter), a narrower size distribution, and a more spherical shape. Sustained drug release was observed from the Lys-αTS/CUR NA for five days at a normal physiological pH (pH 7.4). The developed Lys-αTS/CUR NA showed enhanced cellular accumulation, antiproliferative effects, and apoptotic efficacies in MDA-MB-231 human breast adenocarcinoma cells. According to the results of optical imaging test in the MDA-MB-231 tumor-bearing mouse models, the Lys-αTS/CUR NA-injected group exhibited a more tumor-selective accumulation pattern, rather than being distributed in the normal tissues and organs. The observed tumor targetability of Lys-αTS/CUR was further studied, which revealed improved in vivo anticancer activities (better inhibition of tumor growth and induction of apoptosis in the tumor tissue) after an intravenous administration in the MDA-MB-231 tumor-bearing mouse models. All these results indicate that the newly developed enzyme-based nanocarrier, the Lys-αTS NA, can be a promising candidate for the therapy of breast cancers.